Represents Fantasi Seksual dalam Film Dear David dengan Analisis Naratif Tzevetan Todorov - Arief Rachman Susilo; Dewi Sri Andika Rusmana; Novan Andrianto (Universitas Merdeka Malang, 2024)
The aim of this research is to describe the representation of sexual meaning in the film